2022
DOI: 10.3390/ijerph19148863
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Medical Conditions: A Systematic Literature Review of a Silent Contributor to Adult Drowning

Abstract: Medical conditions can increase drowning risk. No prior study has systematically reviewed the published evidence globally regarding medical conditions and drowning risk for adults. MEDLINE (Ovid), PubMed, EMBASE, Scopus, PsycINFO (ProQuest) and SPORTDiscus databases were searched for original research published between 1 January 2005 and 31 October 2021 that reported adult (≥15 years) fatal or non-fatal drowning of all intents and pre-existing medical conditions. Conditions were grouped into the relevant Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Cardiac arrhythmias, especially of genetical origin, may explain deaths in water occurring without an apparent cause (Lunetta, 2022). In a systematic literature review, Peden et al (2022) concluded that drowning occurs in people with existing medical conditions, yet relatively few studies have documented the risk. Diseases of the nervous system (39%), mental and behavioral conditions (37%) and diseases of the circulatory system (30%) were the most common categories of preexisting medical conditions.…”
Section: Cause and Manner Of Deathmentioning
confidence: 99%
“…Cardiac arrhythmias, especially of genetical origin, may explain deaths in water occurring without an apparent cause (Lunetta, 2022). In a systematic literature review, Peden et al (2022) concluded that drowning occurs in people with existing medical conditions, yet relatively few studies have documented the risk. Diseases of the nervous system (39%), mental and behavioral conditions (37%) and diseases of the circulatory system (30%) were the most common categories of preexisting medical conditions.…”
Section: Cause and Manner Of Deathmentioning
confidence: 99%
“…But this systematic review concluded that limited evidence does not support these as common death mechanisms. A new study classified the pre-existing medical conditions of fatal or non-fatal drowning as diseases of the nervous system, mental and behavioral conditions and diseases of the circulatory system [ 10 ].…”
Section: Introductionmentioning
confidence: 99%